ChemInform Abstract: Supertetrahedral Networks and Lithium‐Ion Mobility in Li2SiP2 and LiSi2P3. Issue 51 (5th December 2016) - Haffner, Arthur; Braeuniger, Thomas; Johrendt, Dirk
Abstract: Polycrystalline Li2 SiP2 (I) and LiSi2 P3 (II) are prepared by solid state reaction of stoichiometric amounts of the elements at 1123 K and 1223 K (II), resp.